ANALISIS EFEKTIFITAS KEPEMIMPINAN KEPALA SEKOLAH di SMK PAMOR CIKAMPEK - Marjita Matanari; Bintang Simbolon (Jurnal Manajemen Pendidikan, 2018)
Principal as a school leader assumes tremendous responsibility to meet the expectations of various stakeholders. The principal is required to be able to direct, organize, set an example to his subordinates to achieve a common goal that has been established. Effective and efficient principals will be able to create an outstanding school, both academic and non-academic. The purpose of this study is to provide a clearer picture of the achievement of the principal, knowing about the leadership of the principal in achieving goals, and knowing how the leadership communication of the principal in SMK Pamor Cikampek. The approach taken is a qualitative approach descriptive. Data obtained from the field is through observation, interview and documentation. The informants in this study were representative of all 23 determined informants, consist of 6 teachers, 4 staff officers, 1 principal and 12 students. The results of the study that the leadership of the private principal of SMK Pamor Cikampek, has performed its duties and responsibilities well as a principal, and its leadership has been effective and efficient.